Cataract surgery contributes to ocular axis growth of aphakic eyes in infants with complex microphthalmos. Issue 39 (25th September 2020) - Sun, Jinfeng; Zhang, Jing; Dai, Yunhai; Wan, Xiaomei; Xie, Lixin
Abstract : Abstract: To observe the ocular axis, visual acuity and intraocular pressure (IOP) of aphakic eye in infants with congenital cataract and complex microphthalmos after first-stage cataract surgery. This retrospective study included infants with congenital cataract and operated at the Qingdao Eye Hospital between January 2010 and December 2014. The infants were divided into 2 groups: preoperative axial length <18 mm (microphthalmos) or ≥18 mm (controls). Follow-up lasted 24 months; visual acuity, axial length, and IOP were evaluated. There were 28 infants (55 eyes) in the microphthalmos group and 35 (61 eyes) in the control group. The preoperative visual acuity was negative for optokinetic nystagmus, while the postoperative visual acuity was positive for optokinetic nystagmus in both groups. The growth rate was higher in the microphthalmos group (1.4 ± 0.8 vs 0.8 ± 0.4 mm/yr, P  < .001 vs controls). The axial length was smaller in the microphthalmos group at all time points compared with the control group (all P  < .001). There was no changes in IOP in the microphthalmos group from baseline to 24 months (P = .147), but the IOP was slightly decreased in the control group ( P  = .015). Cataract surgery may contribute to ocular axis growth in infants with complex microphthalmos.